2018
DOI: 10.1093/aob/mcx139
|View full text |Cite
|
Sign up to set email alerts
|

Modelling temporal variation of parameters used in two photosynthesis models: influence of fruit load and girdling on leaf photosynthesis in fruit-bearing branches of apple

Abstract: The present study proposed a way to model the photosynthesis rate by temporal and environmental variables only. A proper validation of this model will be necessary to extend its utilization and appreciate its predictive capacity fully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
4
16
1
Order By: Relevance
“…Many studies have found that phloem girdling reduces the net photosynthetic rate (Pn) of plant leaves 23 . Sala et al 24 showed that phloem girdling influenced the rate of photosynthetic assimilation, and Poirier-Pocovi et al 25 showed that phloem girdling reduced the photosynthesis rate of leaves. Similar findings were also shown in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that phloem girdling reduces the net photosynthetic rate (Pn) of plant leaves 23 . Sala et al 24 showed that phloem girdling influenced the rate of photosynthetic assimilation, and Poirier-Pocovi et al 25 showed that phloem girdling reduced the photosynthesis rate of leaves. Similar findings were also shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the plant might avoid absorbing too much light by reducing the content of photosynthetic pigments. This reaction is the feedback regulation according to the source-sink relation 25 . The application of modifiers improved the photosynthesis of leaves because the chlorophyll content was significantly increased, and the effect of the application of organic polymer compound modifier after stem girdling was more obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Remobilization and storage of nonstructural carbon after phloem transport manipulation in trees also partially drive alterations in respiratory rates (Figure 3, interactions C & F), which are consistently higher upstream and lower downstream in girdled (Domec and Pruyn, 2008;Maier et al, 2010;Maunoury-Danger et al, 2010), compressed (Henriksson et al, 2015), and chilled stems . Leaf respiration has also been shown to increase after girdling (Maunoury-Danger et al, 2010;Poirier-Pocovi et al, 2018) and phloem chilling . These changes in respiration rates result from a combination of changes in metabolic demand to fuel starch biosynthesis or hydrolysis (Figure 3, interaction F), and changes in growth respiration (Figure 3, interaction 6).…”
Section: Impacts Of Phloem Transport Manipulations On Carbon Dynamicsmentioning
confidence: 99%
“…Thus, caution must be exercised when extrapolating from studies of herbaceous plants to infer carbon dynamics and use in trees. Indeed, evidence from past phloem transport manipulations suggests that, like herbaceous plants, trees actively manage source and sink tissues (i.e., Poirier-Pocovi et al, 2018), thus they are not adequately represented by the prevailing modeling paradigm, that models sink activity as a proportion of source activity (Friend et al, 1997;Cramer et al, 2001;Smith et al, 2001;Ito and Oikawa, 2002;Sitch et al, 2003;Krinner et al, 2005;Inatomi et al, 2010;Tian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By simulating light-response curves of photosynthesis (A n -I curve), NH model has been widely used to obtain key photosynthetic characteristics (e.g., the maximum net photosynthetic rate, A nmax ; light compensation point when A n = 0, I c ; dark respiration rate, R d ) for various species under different environmental conditions (e.g., Ögren & Evans, 1993;Thornley, 1998;Ye, 2007;Aspinwall et al, 2011;dos Santos et al, 2013;Mayoral et al, 2015;Sun et al, 2015;Park et al, 2016;Quiroz et al, 2017;Yao et al, 2017;Xu et al, 2019;Yang et al, 2020;Ye et al, 2020). Significant difference between observed A nmax values and that estimated by NH model for various species has been widely reported (e.g., Chen et al, 2011;dos Santos et al, 2013;Lobo et al, 2014;Ogawa, 2015;Sun et al, 2015;Quiroz et al, 2017;Poirier-Pocovi et al, 2018;Ye et al, 2020). This long-standing challenge has been resolved by an A n -I model, which adopts a nonasymptotic function and can accurately reproduce A n -I curve over light-limited, lightsaturated and photoinhibitory I levels (Ye et al, 2013) (hereafter, Ye model).…”
Section: Introductionmentioning
confidence: 99%